Adolescent Gender Disparities Within Nonformal Islamic Education Majelis Taklim Participation: Disparitas Gender Remaja Dalam Partisipasi Pendidikan Islam Nonformal Majelis Taklim - chicy oktavia; Albertos Damni (Halaqa: Islamic Education Journal, 2026)
General Background Majelis taklim serves as a fundamental institution fostering social cohesion and character development. Specific Background Current religious gatherings across Koto Tengah Village exhibit severe demographic imbalances, predominantly comprising adult women while largely excluding younger demographics. Knowledge Gap Previous literature inadequately addresses how deeply embedded gender roles shape youth involvement concerning these traditional forums through a social constructionist framework. Aims This qualitative case study analyzes youth involvement levels and perceptions regarding community religious gatherings through a socially constructed lens. Results Data gathered through interviews and observations demonstrate remarkably low youth attendance, particularly among boys. The primary deterrent is the prevailing social construct branding the forum exclusively for mothers, compounded by monotonous instructional strategies, insufficient community support, and a generational preference for digital media. Novelty This research distinctly applies social construction theory to deconstruct demographic disparities throughout contemporary religious pedagogy. Implications Communities and policymakers must redesign instructional strategies incorporating digital media and inclusive practices to dismantle stereotypes and revitalize youth engagement. Highlights Societal constructs restrict youth involvement regarding traditional religious gatherings primarily toward adult females. Monotonous instructional methods alongside absent community support severely deter male teenagers from attending. Integrating interactive digital media and relatable speakers revitalizes youth engagement across community learning. Keywords Social Construction Theory; Youth Involvement; Religious Gatherings; Digital Media; Gender Roles